19 The Efficacy, Safety and Acceptability of Non-Pharmacologic Therapy for Orthostatic Hypotension in Older People: A Mixed Methods Study. (20th December 2019) - Frith, James; Robinson, Lisa; Newton, Julia
Abstract: Introduction: First-line treatment for OH is typically with non-pharmacologic therapy. However, the current evidence base is poor, particularly in older people. Aim: Determine the safety, efficacy and acceptability of single and combination therapies for OH in older people. Methods: A three-stage, mixed-methods study consisting of a phase 2 efficacy study with a nested qualitative study. Stage One calculated response rates to therapy (defined as an improvement in standing systolic blood pressure (SSBP) by ≥10 mmHg). Stage Two explored the tolerability of therapies in qualitative interviews. Stage Three evaluated response rates to combinations of the most efficacious and tolerable therapies. All participants were aged ≥60 years, had OH and were recruited from a UK Falls and Syncope Service. Results: Stage One. Response rates to therapies were evaluated in 25 older people (74 years, 60-92): Bolus-water drinking 56% (95%CI 35, 76); abdominal compression 52% (95%CI 31, 72), physical counter-maneuvers 44% (PCM, 95%CI 24, 65), full-leg length compression 32% (95%CI 15, 54). Stage Two. PCM was considered an acceptable therapy as no equipment is required, is only needed during postural change and can be performed conspicuously. Water was largely acceptable but there were concerns around urinary frequency. Compression stockings were considered unacceptable due to cosmesis, practicalities and discomfort. There were mixed views on the tolerability of abdominal compression. There were no adverse events. Stage Three. Response rates to combination therapy were evaluated in 37 older people (71 years, 60-94). Bolus water drinking + PCM 38% (95%CI 22, 55); water + PCM + abdominal compression 46% (95%CI 29, 63). Conclusions: Due to its superior efficacy, safety and acceptability, bolus water drinking should become standard first-line therapy. Conversely, compression stockings should be disregarded in this population, as they are the least efficacious and most unacceptable treatment. Surprisingly, there is no additional benefit of combining therapies.